The amber spyglass - Pullman, Philip, 1946- (London : Scholastic, 2011)
Will and Lyra, whose fates are bound together by powers beyond their own worlds, have been violently separated. But they must find each other, for ahead of them lies the greatest war that has ever been - and a journey to a dark place from which no one has ever returned...
Originally published: 2000.
Keywords: Belacqua, Lyra (Fictitious character) -- Juvenile fiction; Parry, Will (Fictitious character) -- Juvenile fiction; Fantastic fiction; Children's stories